Evaluation of sustainable development for low-volume roads in Sarawak - Ron Aldrino Chan alias Ron Buking,; Muhamad Nazri Borhan,; Riza Atiq Abdullah O.K. Rahmat, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The national socio-economic development programme prioritises rural development, and the state of Sarawak requires many rural roads to connect existing villages to the main roads. This programme can be achieved by upgrading existing non-standard access roads or constructing new access roads. The current challenges and issues related to the sustainable development of low-volume roads (LVRs) in the Malaysian state of Sarawak were investigated in this study. The key goals of the study were to understand the challenges of sustainable development in Low Volume Roads (LVRs) in Sarawak using expert interviews as well as surveys on experienced engineers. It aimed at clarifying what LVRs are, highlighting challenges to do with designing and planning them, and also discussing pavement design aspects. The data for the research was collected through interviews with experts in state Public Work Department (PWD) and consultants with more than 15 years’ experience in road planning and construction. An online questionnaire was distributed and it targeted government agencies, consultants, contractors, with 52 respondents out of 200 possible. This helped to identify important problems associated with LVR development; it stressed that a proper knowledge of LVR design, planning difficulties and those specific concerning pavement designs is needed among professionals within Sarawak road building industry. Based on the findings, immediate need for actions was required to be taken by road agencies to investigate the development and appropriate design of LVRs also to record and gather historical data on current LVRs for further improvement.